Fostering ethical conduct through psychological safety : line managers are key to creating safe spaces for employees to discuss concerns - Ferrère, Antoine; Rider, Chris; Renerte, Baiba; Edmondson, Amy (MIT Sloan Management Review, 2022)
New research finds that reporting on unethical conduct in the workplace is linked to employees’ degree of psychological safety. Those with lower scores on a measure of psychological safety were less likely to report unethical behavior through effective channels — but were also more likely to observe more instances of unethical behavior. The authors argue that a healthy organizational culture is one in which speaking up and listening go hand in hand and thereby reinforce ethical standards.